Intra and Interpersonal Skills of Gen Z Teachers: Exploring Issues and Solutions for Becoming a Professional Teacher - Hilhamsyah Hilhamsyah; Suyatno Suyatno; Sri Tutur Martaningsih (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2026)
Gen Z teachers have high technological skills but face challenges in intra- and interpersonal competencies, potentially affecting teaching quality and professionalism. This study aims to identify the weaknesses in these skills and the strategies used by Gen Z teachers to improve them in support of their professional development. Using a qualitative approach, data were collected through interviews. Informants included five Gen Z teachers, an education coordinator, and a school principal, selected through purposive sampling. Data were analyzed using the steps of data collection, reduction, presentation, and conclusion. The findings reveal that Gen Z teachers at SD Muhammadiyah Yogyakarta face intrapersonal challenges such as emotional vulnerability, mood instability, and difficulty adapting to systemic changes. Interpersonal challenges include limited social interaction, generational gaps, and feeling undervalued by students. However, teachers make efforts to improve through self-development, emotional regulation, and seeking broader educational insights. Interpersonal improvements are pursued through collaboration, empathy, and support from their environment. These findings highlight the need for educational institutions to address these challenges through psychological support, reflective practices, and professional training programs tailored to Gen Z teachers’ needs, ensuring sustainable professional growth.